Minimum Wages, State Ownership, and Corporate Environmental Policies - Chen, Tao; Xiong, Xi; Zou, Kunru (Journal of Financial and Quantitative Analysis, 2025)
Abstract Exploring the minimum wage policy discontinuities at county borders, we find that minimum wage hikes induce industrial firms to pollute more and reduce their abatement efforts. State ownership mitigates these negative effects, suggesting its role in addressing externality. The adverse environmental impacts are attenuated by the staggered increase in pollution discharge fees across provinces. These effects are stronger for firms with higher minimum wage sensitivity, lower market power, and greater financial constraints, and for firms that are the subsidiaries of nonlisted companies. Overall, our findings highlight the unintended environmental consequences of labor market policies.